Peripheral visions : politics, society, and the challenges of modernity in Yucatan - Terry, Edward Davis (University of Alabama Press, 2010)
Yucatan has been called "a world apart"--Cut off from the rest of Mexico by geography and culture. Yet, despite its peripheral location, the region experienced substantial change in the decades after independence. As elsewhere in Mexico, apostles of modernization introduced policies intended to remold Yucatan in the image of the advanced nations of the day. Indeed, modernizing change began in the late colonial era and continued throughout the 19th century as traditional patterns of land tenure were altered and efforts were made to divest the Catholic Church of its wealth and political and inte